Macroeconomic Determinants of Foreign Trade in Nepal - Lekhak, Deepesh; Shrestha, Sushma (The Journal of Economic Concerns, 2025)
Nepal faces persistent challenges in its foreign trade, including weak infrastructures, limited productive capacity, and heavy reliance on imported raw materials. These challenges constrain export competitiveness and growth. Remittance inflows in Nepal have been increasing steadily each year. However, a significant portion of these inflows is primarily spent on consumption and non-productive investments. Furthermore, Population growth and exchange rate volatility also have impacts on foreign trade. It underscores the necessity to systematically analyze the impact of key macroeconomic determinants on Nepal’s foreign trade. This study investigates the role of key macroeconomic variables on foreign trade of Nepal using post-liberalization data from 1991/92 to 2023/24 for empirical analysis. An Autoregressive Distributed Lag (ARDL) model is used to analyze the relationship between foreign trade and key macroeconomic determinants. This study found that economic growth positively affects total trade, including imports and exports. Similarly, population has positive effects on exports and total foreign trade, whereas population does not have significant effect on imports. Furthermore, remittance inflows have significant positive impacts on imports and total foreign trade. However, it is found that remittance inflows do not affect exports substantially. The exchange rate volatility has been found to disrupt trade. The autoregressive persistence of macroeconomic variables showed the critical need for stability and continuity in trade policies.